Analysis of Factors Inhibiting Digital Village Development in Indonesia (Oratio Directa, 2024)
The national target of achieving comprehensive digital village development in Indonesia remains a major task for government and village communities. Various obstacles and challenges affect its implementation. This study explains the factors inhibiting digital village programs. It applies an exploratory qualitative approach and collects secondary data through a literature review. The findings show that digital village development is mainly constrained by the quality of village human resources, limited facilities and infrastructure, and insufficient social and institutional support from stakeholders.
Keywords: Digital village; Digital transformation; Human resources; Digital infrastructure; Stakeholder support